Proposal for the creation of an occupational health documentation centre for the Health and Work Programme in Central America of the National University, Costa Rica. - Solís Rojas, Ana Lucrecia (2012)
This paper summarizes the final work of graduation on the proposal to create a documentation center at the National University of Costa Rica. It presents the general and specific objectives that structured the research, the methodology used, the subjects and sources of information; and finally, the conclusions and recommendations found.